THE RELATIONSHIP OF SMOKING HABITS WITH HYPERTENSION INCIDENCE IN MEN AGE 20-40 YEARS IN THE WORK AREA OF THE BINTARA HEALTH CENTER - Dilla, Andrini Ratna; Indrawati, Lina; Pelawi, Arabta M. Peraten (Rena Cipta Mandiri, 2025)
Hypertension is a non-communicable disease until now dubbed as The Silent Killer because the symptoms are unknown and even often do not show symptoms without complaints. Hypertension is a condition in which a person's blood pressure, systolic ≥140 mmHg and diastolic ≥90 mmHg. Hypertension at the age of 20-44 years, especially in men, the main cause is a lifestyle such as smoking Smoking is one of the risk factors that can cause an increase in blood pressure. Cigarettes contain 400 chemical substances with 200 types of them being carcinogenic. Carbon monoxide and nicotine gases produced by cigarettes, cause the walls of blood vessels to narrow so that the heart has to pump faster and blood pressure increases significantly.